Study Several Biochemical Parameters into Patientas with Hepatitis B Virus (Global Journal of Medical Research, 2013)
Objective: Hepatitis B virus infections is widely seen all through the world. Disorder in the antioxidant system and oxidative stress may play a role in the pathogenesis of chronic liver diseases. The aim of this study was to estimate the oxidant/antioxidant status in patients with HBV positive group, patients with HBV negative and compared to control group. Material and Methods: Thirty six patients with HBV positive group, Thirty six patients with HBV negative and compared to thirty control group were included in this study. Glutathione, superoxide dismutase (SOD) activities, malondialdehyde (MDA), Vit C, Vit E and albumin levels were measured in all patients and control group specthrophotometrically. Results: SOD activity, GSH, VitC, Vit E and albumin were significantly lower in patients with HBV positive group when compared to patients with HBV negative and control group. However, MDA levels was increased in each patient group as compared to the control group. Conclusion: The current study supposed that deficiency of antioxidant barrier may cause oxidative stress in patients with HBV, and may be antioxidant treatment should be useful for these patients.
Keywords: hbv; antioxidant enzymes; malondialdehyde; vit c and vit e